2013
DOI: 10.1586/egh.13.4
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors and stress in inflammatory bowel disease

Abstract: The role of psychological distress and personality as predisposing factors for the development of inflammatory bowel disease (IBD) remains controversial. Attempts to investigate the role of psychological factors in IBD exhibited rather conflicting results. Among the studies concerning the effects of stress or depression on the course of IBD, the majority suggest that stress worsened IBD, the rest giving either negative or inconclusive results. However, application of strategies, including avoidance of coping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 100 publications
0
25
1
2
Order By: Relevance
“…Symptoms of anxiety and depression are common with IBD, even in younger patients. There is consistent evidence for a contribution of psychological factors to IBD disease course, especially stress in UC and depressive symptoms in CD 25. Stress can also exacerbate symptoms in CD by lowering pain thresholds in internal organs, thus increasing the sense of it and decreasing mucosal barrier function 25.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of anxiety and depression are common with IBD, even in younger patients. There is consistent evidence for a contribution of psychological factors to IBD disease course, especially stress in UC and depressive symptoms in CD 25. Stress can also exacerbate symptoms in CD by lowering pain thresholds in internal organs, thus increasing the sense of it and decreasing mucosal barrier function 25.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, the composition of the microbiota is substantially influenced by diet and other life style factors [170,171], and accordingly, dietary changes may contribute to the pathomechanism of IBD. Indeed, it was demonstrated that consumption of a diet high in saturated (milk derived)-fat promoted colitis in IL-10 knock out mice [172].…”
Section: Environmental Factorsmentioning
confidence: 95%
“…Although there have been review papers which have summarised the psychosocial issues associated with IBD (e.g., , Triantafillidis et al 2013, Sainsbury et al, 2006, these have not been systematic, a systematic review of this research is, therefore, timely.…”
Section: Accepted Manuscriptmentioning
confidence: 99%